Analisa Kombinasi Chain Code Dan Single Linkage Clustering Dalam Mengidentifikasi Karakter - Ainun Naimah Pulungan; Herlina Harahap; Rosyidah Siregar (SEMINAR NASIONAL TEKNOLOGI INFORMASI & KOMUNIKASI, 2021)
Character recognition (Optical Character Recognition) is pattern recognition. One method of pattern recognition that is widely used is Single Linkage Clustering and Chain Code whose system works like the human brain which can recognize patterns after training on some of the examples given. The final project prioritizes pattern recognition on characters. To get a pattern on each character, some features of the character itself are needed. The features taken on a character include Perimeter, Area, Shape Factor, Roundness for SLC and Chain Map for Chain Code. Feature retrieval using Single Linkage Clustering and Chain Code methods to be able to distinguish the shapes of the segments according to the given parameters.